The Influence of Social Media Marketing and Service Quality on Repurchase Intention Mediated by Customer Satisfaction on Umrah Packages - Suyandra, Isra Dharma; Syafrizal, Syafrizal; Sari, Dessy Kurnia (PINISI Discretion Review, 2025)
The desire of the community to perform the Umrah pilgrimage to the holy land is increasing and becoming a market segment for Umrah entrepreneurs. At this time, there are so many Umrah bureaus emerging which then have implications for the tight competition in Umrah pilgrimage travel, requiring companies to be creative and innovative in order to survive. This study aims to test the influence of social media marketing and service quality on repurchase intention mediated by customer satisfaction on Umrah packages at PT. Haura Abadan Wisata. The approach used in the study is a quantitative approach using SEM-PLS (Structural Equation Modeling - Partial Least Square). The results of the study indicate that social media marketing, service quality and customer satisfaction show a significant influence on repurchase intention. Social media marketing shows an insignificant influence on customer satisfaction. Service quality shows a significant influence on customer satisfaction. Social media marketing shows an insignificant influence on repurchase intention mediated by customer satisfaction. Service quality shows a significant influence on repurchase intention mediated by customer satisfaction on Umrah packages at PT. Haura Abadan Wisata